2012
DOI: 10.1128/iai.06031-11
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Potential of Campylobacter ureolyticus

Abstract: The recent detection and isolation of the aflagellate Campylobacter ureolyticus (previously known as Bacteroides ureolyticus) from intestinal biopsy specimens and fecal samples of children with newly diagnosed Crohn's disease led us to investigate the pathogenic potential of this bacterium. Adherence and gentamicin protection assays were employed to quantify the levels of adherence to and invasion into host cells. C. ureolyticus UNSWCD was able to adhere to the Caco-2 intestinal epithelial cell line with a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…This implication was confirmed by their further studies on C. ureolyticus pathogenicity and growth control imposed on the species present in the intestine (O'Donovan et al, 2014). Other studies indicated that this emerging pathogen can cause a gastrointestinal illness via destruction of cell structures (Garmory and Titball, 2004), relocating across the cell using various proteins such as zona occludens toxin (Zot) and secreted fibronectin-binding proteins (CadF and FlpA) (Bullman et al, 2013), or forming biofilms (Burgos-Portugal et al, 2012). Because the studies regarding the role of Campylobacter in gastroenteritis are still in their infancy, more research is needed to fully understand the relation between Campylobacter species and gastrointestinal diseases.…”
Section: Gastroenteritismentioning
confidence: 81%
“…This implication was confirmed by their further studies on C. ureolyticus pathogenicity and growth control imposed on the species present in the intestine (O'Donovan et al, 2014). Other studies indicated that this emerging pathogen can cause a gastrointestinal illness via destruction of cell structures (Garmory and Titball, 2004), relocating across the cell using various proteins such as zona occludens toxin (Zot) and secreted fibronectin-binding proteins (CadF and FlpA) (Bullman et al, 2013), or forming biofilms (Burgos-Portugal et al, 2012). Because the studies regarding the role of Campylobacter in gastroenteritis are still in their infancy, more research is needed to fully understand the relation between Campylobacter species and gastrointestinal diseases.…”
Section: Gastroenteritismentioning
confidence: 81%
“…The release of high levels of toxins causes cells to lyse as pores formed by the toxin allow cytoplasmic contents to leak out of the cell 71 . In relation to this, an S-layer RTX protein was shown to be secreted by the C. ureolyticus strain UNSWCD, which had been isolated from an intestinal biopsy of a young Crohn disease patient 72 . These proteins are typically associated with complement resistance as well as providing structures that enable bacterial adherence to the host cell 73 …”
Section: Secretome and Virulence Factors/toxinsmentioning
confidence: 99%
“…H. pylori and C. ureolyticus are two bacterial species primarily associated to the gastrointestinal microbiota in humans [12,29]. The occurrence of H. pylori in the oral cavity has been shown in numerous studies and the oral cavity has been claimed to function as a reservoir for transmittance to the stomach after H. pylori eradication and treatment of peptic ulcers [6].…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter ureolyticus is another highly ureolytic bacterial species that is suggested to be a gastrointestinal pathogen [12,13]. It is occasionally isolated from the dental plaque of periodontitis patients [14].…”
Section: Introductionmentioning
confidence: 99%